2003
DOI: 10.1038/sj.sc.3101407
|View full text |Cite
|
Sign up to set email alerts
|

Gender related differences in pain in spinal cord injured individuals

Abstract: Study design: Out of a population of 456 patients with spinal cord injuries (SCI), 130 having pain were selected after matching, based on gender, age, American Spinal Injury Association (ASIA) impairment grade and level of lesion. Objective: To investigate whether gender di erences with regard to pain perception and prevalence exist in a population of patients following spinal cord injury. Setting: Spinalis SCI Unit (out-patient clinic), Stockholm, Sweden. Method: 130 patients su ering from pain were assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…An earlier study has reported that women have higher prevalence of nociceptive pain after SCI. 11 It is possible that the results would have shown such difference also in this study if we had chosen to ask for neuropathic pain of significant importance rather than for neuropathic pain in general.…”
Section: Importance Of Studied Parameters For the Occurrence Of Neuromentioning
confidence: 77%
See 2 more Smart Citations
“…An earlier study has reported that women have higher prevalence of nociceptive pain after SCI. 11 It is possible that the results would have shown such difference also in this study if we had chosen to ask for neuropathic pain of significant importance rather than for neuropathic pain in general.…”
Section: Importance Of Studied Parameters For the Occurrence Of Neuromentioning
confidence: 77%
“…In their studies, Siddall et al 4,9 showed no correlation between either injury level or completeness of injury. Previous studies 10 showed that the incidence of neuropathic pain after SCI correlates positively with increasing age at injury and gender, 11 but could not demonstrate such associations with injury level and completeness of injury.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…11 We also did not find any significant differences in length of stay in rehabilitation unit, disability at admission and disability at discharge between men and women with NTSCL. Women with SCI tend to suffer more from pain 12 and depression. 13 In the present study, we did not notice any significant differences between men and women in these complications.…”
Section: Discussionmentioning
confidence: 99%
“…A higher female prevalence of nociceptive pain after SCI has been reported. 16,24 One possibility is that the males who suffered a traumatic SCI belong to a male subgroup that are more prone to develop neuropathic pain than other men, and are perhaps associated with a more risky way of living. This would not apply to men with nontraumatic SCI.…”
Section: Methodological Issuesmentioning
confidence: 99%